2011
DOI: 10.2174/187152011796817637
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Expression of Pax-5 and FAK1 in Metastasis

Abstract: The Pax-5 gene encodes a B-cell-specific activator protein (BSAP) that plays a key role in B lymphocyte differentiation and embryogenesis. The deregulation of this transcription factor is also linked to B cell malignancies and recently to other cancers. More specifically, the downstream effects of Pax-5 promote cell-cell interactions and mediate the activation of adhesion genes which result in an epithelial phenotypic behavior of human carcinoma cells. To gain a better understanding of Pax-5-mediated gene regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…Intriguingly, Pax-5 seems to confer an anti-proliferative effect in most carcinomas studied in contrast to its stimulatory effect on B cell proliferation 21, 34. Most importantly, we and others show that Pax-5 expression reduces mesenchymal marker expression, colony formation and migratory capabilities while concomitantly inducing epithelial characteristics in invasive breast carcinoma cells 21, 22, 35.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…Intriguingly, Pax-5 seems to confer an anti-proliferative effect in most carcinomas studied in contrast to its stimulatory effect on B cell proliferation 21, 34. Most importantly, we and others show that Pax-5 expression reduces mesenchymal marker expression, colony formation and migratory capabilities while concomitantly inducing epithelial characteristics in invasive breast carcinoma cells 21, 22, 35.…”
Section: Introductionmentioning
confidence: 51%
“…However, we have previously reported that the expression profiles of pro-epithelial factor Pax-5 inversely correlate with those from pro-malignant FAK 22. We therefore set out to establish and elucidate a possible regulatory mechanism between the Pax-5 transcription factor and FAK in breast cancer processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, Pax-5 expression correlates with increasing disease malignancy. Furthermore, recent findings have shown that Pax-5 expression is present in breast cancer (18,19) and is thought to be involved in metastatic progression (20). Taken together, these results add to the growing body of evidence that implicates Pax-5 activity in diverse nonhematopoietic solid tumor malignancies.…”
Section: Pax-5 Expression In Nonhematopoietic Cancersmentioning
confidence: 58%
“…Of interest, a gene expression microarray analysis revealed a 100-fold overexpression of Pax-5 in breast cancer cells that metastasized to lymph nodes compared with the primary tumor (27). Moreover, Pax-5 has been shown to suppress the expression of the proinvasive focal adhesion kinase, reminiscent of the mesenchymal-epithelial transition (20). Collectively, these findings suggest the involvement of Pax-5 in breast cancer and its progression to metastasis.…”
Section: Dichotomous Roles Of Pax-5 In Metastasismentioning
confidence: 96%